Optimizing Post-Harvest Preservation of Shallots (Allium Aascalonicum L) through the Application of Co-60 Gamma Ray Irradiation Technology - Sarjono, Arianto Passalli; Indriastuti, Alfiah; Azis, Hijrah Amaliah; Ramdani, Nurfika; Mustam, Mariaulfa; Amin, Ida Ifdaliah; Wahab, Nurhikmah; Bangun, Daniel (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2024)
Shallots are an important food commodity for the needs of various Indonesian cuisines and other uses that are widely utilized. However, currently shallot farmers complain about post-harvest shallots that are easily damaged such as rotting, wrinkling, porous, root growth and fungal growth. To reduce this damage, preservation is needed. One alternative technology is Co-60 Gamma Ray Irradiation based on the principle of electromagnetic radiation that produces high-energy photons that cause ionization and excitation in the material it passes through. The nature of Gamma rays used in the preservation process has great penetrating power and does not cause temperature changes in the irradiated food. The purpose of this study was to determine the effect of Co-60 gamma ray irradiation on the optimization of the shelf life of post-harvest preservation of shallots with variations in control doses: low, medium and high, variations in temperature and quality parameters. The method of this research stage is: 1) Sample preparation. 2) Gamma Ray Irradiation of Co-60 with variation of control dose: low, medium and high 3) Analysis of temperature measurement and measurement of quality parameters (water content, weight loss, damage and hardness) against the irradiation dose. The results showed that gamma ray irradiation of Co-60 affected the length of shoots based on variation of dose and temperature, namely on day 1 and day 14 the combination of 650Gy treatment at 350C had the smallest shoot length, water content was relatively high, weight loss was relatively small, damage was relatively small and hardness was relatively high.